TRANSLATION POSSIBILITIES OF CONTEXTUAL MODIFICATIONS OF PHRASEOLOGICAL UNITS - Elena Arsenteva; Albina Kayumova (Proverbium, 2012)
The article is devoted to the problem of translation of modified phraseological units including proverbs. A short review of works of European scientists concerning the difficulties that translators face is presented. Some interesting examples of modified idioms and proverbs taken from the novels “The Moonstone” and “The Woman in White” by W. Collins serve as good illustrations of the challenge that translators have to accept. The training algorithm is put forward that beginners should follow in order to avoid typical mistakes while translating modified idioms and proverbs.